MENINGKATKAN KOMPETENSI GURU DALAM MENYUSUN BUTIR SOAL MELALUI KEGIATAN WORKSHOP DI SEKOLAH DASAR - Gusmarni Gusmarni (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2019)
This research was conducted at 004 Koto Kombu public elementary school. The subjects of this study were all 13 teachers consisting of 6 female teachers and 7 male teachers. The design of this study uses school action research which aims to improve teacher competency in compiling items through workshop activities. The study was planned in 2 cycles with stages of planning, implementation, observation and reflection. The results showed, in the effect of the suitability of the questions with the learning objectives in the initial data to the first cycle increased by 15.7% while the increase in the initial data to the second cycle increased by 27.6%. Asfect suitability of the questions with the content (material), from the initial data to the first cycle increased by 17.7% while the initial data to the second cycle increased by 23.3%. For the language use effect, from the initial data to the first cycle increased by 12.9%, while the data from the second cycle increased by 28.2%. Can the researchers conclude that through the workshop activities can improve teacher competence in compiling items in elementary school